2017
DOI: 10.7554/elife.25174
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure-guided design of dynapyrazoles, cell-permeable dynein inhibitors with a unique mode of action

Abstract: Cytoplasmic dyneins are motor proteins in the AAA+ superfamily that transport cellular cargos toward microtubule minus-ends. Recently, ciliobrevins were reported as selective cell-permeable inhibitors of cytoplasmic dyneins. As is often true for first-in-class inhibitors, the use of ciliobrevins has in part been limited by low potency. Moreover, suboptimal chemical properties, such as the potential to isomerize, have hindered efforts to improve ciliobrevins. Here, we characterized the structure of ciliobrevins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 68 publications
5
58
0
Order By: Relevance
“…We imaged a longer 12-heptad stalk-SRS construct on 13 protofilament microtubules, compared to a 3-heptad construct on 14-protofilament microtubules. To confirm that the structure we observed is representative of full-length dynein bound to microtubules we imaged a human cytoplasmic dynein-1 motor domain construct (DYNC1H1 1230-4646 , (Steinman et al, 2017) bound to microtubules ( Figure S1A ). Grids were frozen in the absence of nucleotide to attain a high-affinity state.…”
Section: Resultsmentioning
confidence: 73%
“…We imaged a longer 12-heptad stalk-SRS construct on 13 protofilament microtubules, compared to a 3-heptad construct on 14-protofilament microtubules. To confirm that the structure we observed is representative of full-length dynein bound to microtubules we imaged a human cytoplasmic dynein-1 motor domain construct (DYNC1H1 1230-4646 , (Steinman et al, 2017) bound to microtubules ( Figure S1A ). Grids were frozen in the absence of nucleotide to attain a high-affinity state.…”
Section: Resultsmentioning
confidence: 73%
“…Under these conditions, we confirmed that ciliobrevin was most active at 50 μM by examining the inhibition of motions of organelles labeled by LysoTracker Red (videos S4 and S5). However, this inhibitor is less active in serum ( 40 ), and we found that in serum, the combination of ciliobrevin and chlorpromazine was toxic to the cell. Because of this information, we performed the experiments without chlorpromazine in serum-free medium for periods of <15 min.…”
Section: Resultsmentioning
confidence: 84%
“…Additional development identified ciliobrevins specific for dynein 2, but even the most potent variants had half-maximal inhibitory concentration (IC 50 ) values >10 mM (See et al, 2016). Recently, isosteres of ciliobrevins were identified with significantly lower IC 50 values, but considerable toxicity was observed at 20 mM, which is only 2-fold above the concentration used for efficient dynein inhibition (Steinman et al, 2017). Thus, smallmolecule inhibitors that target dynein 1 and 2 more potently and exhibit reliable performance would greatly benefit the field.…”
Section: Introductionmentioning
confidence: 99%